A toy story determinants of toy choices of UP CDC parents - Basmayor, Lauren Christine Cruz
Even as the choice of toys during childhood is mainly influenced by parental decision, this study determined factors that contribute to parents' choice of toys for their preschool children. It aimed at answering what demographic attributes of the child influence parental toy choice, specifically the child's age and gender a probable determinants. The objectives of the study were to determine the factors that parents consider in choosing toys; to investigate if the gender of the child influence parents' choices of toys; to find out if the child's age affect parental toy choice; and to explore the other factors that affect choice of toys such as values, family income, and mass media. Forty (40) parents of preschool children form UP CDC were individually interviewed for the study. Qualitative and quantitative methods of analysis were utilized for the treatment of the data. Considerations of parents in choosing toys were identified based on a ranking-type question and open-ended questions during the interview. Chi-square est of independence and phi coefficient were used to analyze the data. Results revealed that there is no sufficient data to prove that neither the child's gender and the child's age group influence parental toy choice. Furthermore, the child's gender and the child's age group revealed weak correlation with toy choice. Open-ended questions on considerations in parental toy choice gave different answers that were grouped into three (3) categories: toy attribute, child's attribute and educational aspect. On the other hand, ranking-type question gave the following order for the considerations of parents in choosing toys: (1) safety, (2) functionality, (3) appropriateness, (4) durability, (5) price, and (6) aesthetics. Parents' sources of ideas about toys include the different forms of mass media such as books, magazines, advertisements, radio, television, and internet.